Biomechanical analysis for the distalisation of the mandibular dentition with anterior alveolar bone loss based on the location of an applied force: A finite element study - Yang Jing; Zhang Qianqian; Zheng Dehua; Hou Fengchun (Australasian Orthodontic Journal)
The present study analysed the tooth movement patterns and stress distribution in patients presenting with anterior alveolar bone loss, associated with the use of force vectors applied from a mini-screw to distalise the mandibular dentition.